2018
DOI: 10.3310/hta22290
|View full text |Cite
|
Sign up to set email alerts
|

What works to increase attendance for diabetic retinopathy screening? An evidence synthesis and economic analysis

Abstract: The National Institute for Health Research Health Technology Assessment programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 185 publications
(746 reference statements)
5
47
0
Order By: Relevance
“…The second study used an extended screening interval of 3 years, and an adherence rate of 91% was observed [ 16 ], which is close to that noted in our investigation. The high adherence rates we report from the screening program in our study may also be explained by having implemented a panel of interventions reported to be favorable for DR screening [ 22 ]. These interventions include facilitating retinal examinations by multiple access points, using telemedicine, giving feedback to diabetologists and general practitioners and sending reminders to patients who failed to attend their follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…The second study used an extended screening interval of 3 years, and an adherence rate of 91% was observed [ 16 ], which is close to that noted in our investigation. The high adherence rates we report from the screening program in our study may also be explained by having implemented a panel of interventions reported to be favorable for DR screening [ 22 ]. These interventions include facilitating retinal examinations by multiple access points, using telemedicine, giving feedback to diabetologists and general practitioners and sending reminders to patients who failed to attend their follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…First, considering that most interventions to promote screening achieve statistically significant increases in screening rates, and that QBE effects have been demonstrated in other socially desirable behaviours (44), we recommend utilisation of QBE as a strategy for policy and practice. The simple act of asking questions about uptake has been used for other health-related behaviours, such as health check attendance and influenza vaccination (44) and may be sufficient to prompt screening, particularly if content and delivery are designed to engage low-attending groups such young adults with T2D (15). Second, 'number of cues' has been identified as a predictor of uptake of pre-pregnancy care for young adult women with T2D (45).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…A range of demographic, clinical and psychosocial barriers to retinal screening have been identified for this group (12), including low general and health literacy, a key issue for ophthalmic education materials which are "consistently" written above recommended levels (13,14). Consequently, healthcare professionals and policymakers have called for development of evidence-based health behaviour change interventions and tailored, age-appropriate messaging which addresses screening barriers and enablers for this group (15,16). Effective interventions to promote health behaviour change have shared elements: content grounded in evidence and underpinned by theoretical constructs; targeting modifiable behavioural and psychosocial determinants of the behaviour, and tailored to the priority population (17).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, screening rates in this priority population are estimated to be 55%, compared with 78% in the general diabetes population [10,11]. A range of barriers to retinal screening have been identified among this group [12][13][14], leading to calls for tailored, age-appropriate intervention [15,16].…”
Section: Introductionmentioning
confidence: 99%